1993
DOI: 10.1007/bf00203105
|View full text |Cite
|
Sign up to set email alerts
|

Diamagnetic anisotropy of sheetsilicates

Abstract: Abstract. The diamagnetic properties of sheetsilicates are studied by measuring the magnetic orientation of micron-sized crystals. In the case of synthetic phlogopite with the average diameter of 0.65 gm and the thickness of 0.2 gm, the alignment of the grains is achieved in the magnetic field below 35 kOe. The planes of the platy single-crystal grains were alignned parallel to the field when the alignment was achieved. The alignment of the grains is realized because the field-induced anisotropic energy, cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 11 publications
2
38
0
Order By: Relevance
“…The effect of parameters M, χ and T on B s , which is expected from Eq. (1), has been systematically examined by measuring common sheet-silicates, such as muscovite, talc and kaolinite (Uyeda et al, 1991(Uyeda et al, , 1993. The results of these experiments confirmed that the field of alignment could be reduced considerably by increasing M or χ , and also by decreasing T , as expected from Eq.…”
Section: Effect Of M χ χ χ χ χ χ χ χ and T On The Alignment Processsupporting
confidence: 58%
See 2 more Smart Citations
“…The effect of parameters M, χ and T on B s , which is expected from Eq. (1), has been systematically examined by measuring common sheet-silicates, such as muscovite, talc and kaolinite (Uyeda et al, 1991(Uyeda et al, , 1993. The results of these experiments confirmed that the field of alignment could be reduced considerably by increasing M or χ , and also by decreasing T , as expected from Eq.…”
Section: Effect Of M χ χ χ χ χ χ χ χ and T On The Alignment Processsupporting
confidence: 58%
“…Alignment of micron-size crystals caused by the anisotropy of magnetic susceptibility χ was recently observed for common rock-forming silicates, namely kaolinite, talc, muscovite and biotite (Uyeda et al, 1991(Uyeda et al, , 1993. The experiment was performed at room temperature (T = 300 K) using liquid ethanol as the dispersing medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic alignment of inorganic materials have been performed on micro-crystals of some nonmetals, such as kaolinite, talc, 5) lepidolite, fluoro-phlogopite, muscovite, 6) graphite, 7) Al 2 O 3 . 8,9) and various ceramic materials.…”
Section: Introductionmentioning
confidence: 99%
“…16) Experimental evaluations of the effects of the parameters which control the magnetic alignment process, discussed above, can be examined quantitatively by adopting the inorganic materials in the alignment experiments. [5][6][7] It was difficult, for example, to alter the value of temperature over a wide range in the experiment using a biological material.…”
Section: Introductionmentioning
confidence: 99%